The impact of Privatisation – Empiric analysis and results in Serbian industry - Nikolic, Ivan; Kovačević, Miladin (Industrija, 2014)
The privatization concept, applied after the 2000 changes, failed to bring the expected performance to Serbian industry. Privatization partly initiated the enterprises restructuring in some fields of manufacturing industry. It brought fresh capital, new technologies and new managerial know-how. However, the result thereof was far weaker than the initially expected. The reasons for the said, but also the end aims of the given process, are analyzed in detail throughout the following article. The research is based on the processing of data from financial statements, submitted by the companies from the Serbian non-financial corporate sector in the period 2002-2007. Panel analysis disclosed the way in which the results of each of the observed ownership forms have changed over time in different sectors and branches of the industry. On the other hand, we also tested the hypothesis according to which privatization effects on the companies’ performances significantly vary depending on the company size, whereby the effects of capital sales model have been implicitly assessed.